Revitalization of old Buildings In The City Of Hebron - Shaheen, Wael (IJIET - International Journal of Innovations in Engineering and Technology, 2019)
Abstract- This paper introduces a longstanding Palestinian City which has exited – and still does – for more than 5000 years, and which is deemed as one of the rare Islamic cities that has managed to maintain its historical architectural heritage, bearing the magnificent touches of past days. Hebron is therefore a major reference in the study of Palestine`s history and of Arabic Islamic civilization in general. Hence, it constitutes an open museum for studying not only the cultural heritage evolution of an Arab City but also its social evolution, with its buildings and urban texture depicting the story of the growth and evolution of families andtribes, social relations and the racial and religious roots of its residents (archive, 2010) The Old Town enjoys a rich architectural heritage. It differs from many other similar cities by the fact that it mainly boasts a popular architectural, with only a few official-style buildings. It is very harmonious architecture, reflecting the social and class harmony of its citizens. Rarely does one find a palace that is architecturally and artistically different from other residential buildings, to the exception of a few Mamluk-style buildings and some mosques, thus making it especially unique. Through various contribution, this paper will attempt to shed light on Hebron`s history and architecture, using a smooth style which facilitates information transfer and delightfully reveals the city`s beauty. It also introduces one of the region`s largest and more successful mass rehabilitation projects (Sherlock, 2010). Although the following articles were drafted scientifically, based on sources, references and annotations, this publication is not intended to underline our scientific capabilities in academic documentation, we have therefore, forsaken all annotations and sufficed ourselves with a select list of sources and references. We hope that this paper would boost public interest in the Old city of Hebron, as well as in Palestine`s another historical center.
Keywords: Revitalization, Hebron, old Buildings